PENDAMPINGAN USAHA PETERNAKAN ITIK PADA KELOMPOK TANI TERNAK DESA LOYOK KECAMATAN SIKUR LOMBOK TIMUR - Dwi Kusuma Purnamasari; Syamsuhaidi Syamsuhaidi; Erwan Erwan; Komang Gede Wiryawan; Sumiati Sumiati; Sri Sulastri (Universitas Mataram, 2022)
Loyok Village is located on the Mount Siu-Kotaraja tourism route which is visited by many local and foreign tourists. This causes the village administrator to hope that Loyok Village can be more advanced to support the tourism program by having superior products in the form of duck meat and eggs. So far, livestock farming, both large and small, is still used as a side business. Livestock rearing is done in free time and with an irregular feeding schedule. This activity aims to disseminate information, increase knowledge and skills in the business of raising ducks independently. Service activities are carried out through providing management materials for raising ducks, local feed ingredients as alternative feed ingredients, providing motivation for raising livestock, and the importance of forming a farmer group in Loyok Village. The service activity was attended by the Village Head and his staff, breeders, and female livestock farmers. Service participants enthusiastically participated in the delivery of material and discussions during service activities. To achieve maximum productivity, ducks must pay attention to cage management, feed formulas that are in accordance with the needs of ducks, and environmental hygiene to avoid ducks being exposed to various kinds of diseases. Several programs resulted from this service activity, including making Loyok Village a fostered village of the Faculty of Animal Husbandry by involving academics in village planning, so that the development of the livestock sector develops in a directed manner. from this service activity is an increase in the knowledge, insight, and enthusiasm of the service participants in increasing the duck farming business.